Rancang Bangun Sistem Perpustakaan Web Universitas Esa Unggul dengan Metode Scrum untuk Pengelolaan Digital - Azzahra, Fayza; Dzikrya, Kaysa; Prabowo, Ary (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
Conventional library systems that are still manual-based often face various obstacles, such as delays in the transaction process, the risk of recording errors, and low efficiency in collection management. This research aims to design and build an integrated web library system at Esa Unggul University by applying the Object Oriented Programming (OOP) approach and Scrum method. The development process is carried out iteratively through the stages of Sprint Planning, Execution, Review, and Retrospective. The system was developed using Python programming language with Flask framework and MySQL database. The main features include book data management, members, loan and return transactions, automatic notifications, and time-based fine calculations. Evaluation was conducted using the Black Box Testing method on 35 scenarios, including input validation, transaction processing, and system resilience to extreme conditions. The test results showed a 100% success rate and a 60% increase in transaction efficiency compared to the manual system. End-user validation showed that the system has a responsive interface, easy to use, and supports digital library management. This research contributes to the digital transformation of libraries and opens up opportunities for development towards mobile platforms and data analytics.